Force Degradation of Intermaxillary Latex Elastics: Comparative In Vitro and In Vivo Study - Lucie Ptáčková; Barbora Ličková; Wanda Urbanová; David Sluka; Klaudia Portašíková; Soňa Chamlarová; Iva Voborná; Ivana Dubovská (Clinical and Experimental Dental Research)
ABSTRACT Objective This study aimed to compare the force degradation of intermaxillary elastics (IE) in vitro and in vivo while stretching the IE to a precise diameter. Materials and Methods IE 3/16″ medium Dentaurum from five different batches of packaging were analyzed. The in vivo study involved 10 volunteers, of which 100 IE were examined. To achieve three times the original diameter of the elastic, the distance between the upper canine and the lower dental arch was measured. Buttons were then placed in the mouth accordingly, and IE and passive aligners were inserted for five sessions of 48 h each. To investigate in vitro, 100 IE were placed in an incubator set at 37°C in a humid environment and stretched three times their diameter. The force of the elastics was measured in both investigations using a force meter at 0, 2, 8, 24, and 48 h. Results In all patients except one, the three times diameter distance extended from the upper canine to the lower second premolar. The force degradation in vivo at 2, 8, 24, and 48 h was 20.58%, 26.78%, 34.81%, and 38.56% and in vitro was 16.38%, 22.83%, 28.32%, and 30.78%. Conclusions The amount of stretching of IE varies for each patient when using standard insertion points. The force of IE decreases exponentially, the force degradation in vivo being higher. The clinician must consider the force decrease when advising the patient of the time interval to change the elastics.